Posterior Chamber Intraocular Lens Dislocation Into the Vitreous in Association With Descemet Stripping Lamellar Keratoplasty. Issue 6 (2nd June 2022) - Rodler, Kristóf Dániel; Pregun, Tamás; András, Bernadett; Pluzsik, Milán Tamás; Hargitai, János; Kerényi, Ágnes
Abstract : Purpose: The purpose of this study was to report 3 cases of a single-piece, acrylic, foldable, modified C loop posterior chamber intraocular lens (PCIOL) dislocated into the vitreous cavity after Descemet stripping automated endothelial keratoplasty (DSAEK). Method: We describe the clinical course and management of the 3 cases in which a previously implanted foldable, single-piece, acrylic posterior chamber intraocular lens with modified C loops dislocated into the vitreous in association with DSAEK. Surgical management consisted of pars plana vitrectomy in each case with either PCIOL repositioning (2 cases) or PCIOL exchange (1 case) and with different fixation methods, combined with repeated DSAEK in 1 case with previous primary graft failure. Results: In 2 cases where the cornea cleared after the DSAEK, the cornea kept its clarity and the PCIOL remained stable. In the third case in which the PCIOL exchange was combined with DSAEK, the cornea only partially cleared up, both the PCIOL and the state of the eye remained stable. Conclusions: PCIOL dislocation is a possible and notable complication that requires attention while performing DSAEK on pseudophakic eyes. Not only plate-haptic silicone but also acrylic, single-piece PCIOLs with modified C loops may dislocate into the vitreous in association with DSAEK in cases with compromised capsular or zonular integrity.